2015
DOI: 10.1177/1362361315577519
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms in young people with autism spectrum disorder attending special schools: Associations with gender, adaptive functioning and autism symptomatology

Abstract: Anxiety-related problems are among the most frequently reported mental health difficulties in autism spectrum disorder. As most research has focused on clinical samples or high-functioning children with autism spectrum disorder, less is known about the factors associated with anxiety in community samples across the ability range. This cross-sectional study examined the association of gender, age, adaptive functioning and autism symptom severity with different caregiver-reported anxiety symptoms. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 77 publications
11
30
0
2
Order By: Relevance
“…In addition, the types of anxiety symptoms that are most common may differ across different developmental periods. For example, higher levels of generalized anxiety and social anxiety symptoms have been associated with an older age and higher levels of separation anxiety symptoms with a younger age in ASD samples (Magiati et al., ; van Steensel et al., ), consistent with developmental changes in the prevalence of anxiety subtypes in the general population (Copeland, Angold, Shanahan, & Costello, ; Van Oort, Greaves‐Lord, Verhulst, Ormel, & Huizink, ). This indicates the need to replicate findings across different age groups.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the types of anxiety symptoms that are most common may differ across different developmental periods. For example, higher levels of generalized anxiety and social anxiety symptoms have been associated with an older age and higher levels of separation anxiety symptoms with a younger age in ASD samples (Magiati et al., ; van Steensel et al., ), consistent with developmental changes in the prevalence of anxiety subtypes in the general population (Copeland, Angold, Shanahan, & Costello, ; Van Oort, Greaves‐Lord, Verhulst, Ormel, & Huizink, ). This indicates the need to replicate findings across different age groups.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, restricted/repetitive behavior may be a reaction to higher levels of anxiety or arousal as a coping mechanism (Rodgers, Glod, Connolly, & McConachie, 2012). Consistently, levels of anxiety have been associated with autistic social impairment (Sukhodolsky et al, 2008), social skill deficits (Bellini, 2006), repetitive and stereotyped behavior (Magiati et al, 2016;Rodgers et al, 2012), and sensory symptoms (Ben-Sasson, Carter, & Briggs-Gowan, 2009) in mostly cross-sectional studies.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, other studies have found that only specific anxiety symptoms (e.g., generalized, separation, and panic-related worries) were associated with higher IQ in individuals with ASD [23]. A similar mixture of findings is also evident regarding the relationship of anxiety in individuals with ASD and verbal abilities [10, 26, 27]. Some evidence suggests that assessment methods (questionnaires versus interviews) contribute to the wide range of estimates, as higher prevalence rates of generalized anxiety are reported in studies that used questionnaires compared to studies that used interviews [28, 29].…”
Section: Prevalence Of Anxiety and Ocd In Autismmentioning
confidence: 80%
“…() found significantly higher levels of psychiatric comorbidity in ASC populations when compared with non‐ASC populations including major mood/depressive disorders, bipolar disorder and psychosis. Particularly high comorbidity concerned multiple anxiety disorders including phobias, separation anxiety disorder, agoraphobia, social phobias, obsessive–compulsive disorder, post‐traumatic stress disorder and generalized anxiety disorders (Magiati et al., ). Mannion et al.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis undertaken by Van Steensel, BĂśgels, and Dirksen () suggested 40% of young people with ASC met the criteria for an anxiety disorder, and Magiati et al. () suggested that people with greater ASC symptomatology that is more effected by the core features of autism are more vulnerable to anxiety‐related difficulties. The intolerance of uncertainty (IU) is defined as a broad dispositional risk factor for the development and maintenance of clinically significant anxiety (Carleton, ).…”
Section: Introductionmentioning
confidence: 99%